Avaliação da importância do gelo marinho antártico sobre a circulação atmosférica e comportamento dos ciclones extratropicais no hemisfério sul - Britto, Ítalo Venceslau (Brasil, 2020)
Antarctic sea ice is considered a fundamental element in the analysis of the global climate, due to its performance as a thermal insulator, registered as heat exchanges between the ocean and the atmosphere. In addition, a distribution of sea ice is an important factor in the formation of transient atmospheric systems, such as extratropical cyclones, especially those originating on the continental edge of Antarctica. Extratropic cyclones are targets for study due to the impact on the weather conditions of the regions where they pass, and savings in the transport of heat, water vapor and time. Therefore, the objective of this study was to evaluate the behavior of extratropic cyclones in the Southern Hemisphere (HS) and the atmospheric circulation in front of the Antarctic sea ice, for the period from 1979 to 2015, through two simulations using the General Circulation Model of the SPEED Atmosphere. One of the simulations, the Antarctic sea ice was removed and the other Antarctic sea ice was maintained, both at a regular rating of 3.75 ° x 3.75 ° and temporal resolution of 24 hours. The data used for the scalable analysis of the atmospheric circulation of the HS were the fields of surface temperature, albedo, sea surface temperature, mean sea level pressure, geopotential height and zonal wind at 200 hPa. For analysis and detection of extratropic cyclones in the HS, use a pressure at medium sea level. The results show that the influence of Antarctic sea ice on atmospheric circulation and extratopic cyclones is clear, considering what happens with the removal of Antarctic sea ice, which can be observed if, as the climatic variables significantly affected, mainly where gradients are more intense; the most common atmospheric patterns showed more intensity in the simulation without ice than in the simulation with ice; and as cyclone responses to the change without ice, if they are stronger and less frequent, or if it was detected in the change with ice. O gelo marinho Antártico é considerado um integrante fundamental ...